Perspective: Advancing the science regarding temporomandibular disorders - Ohrbach, Richard; DaSilva, Alexandre F.; Embree, Mildred C.; Kusiak, John W. (Frontiers in Dental Medicine, 2024)
This Special Issue was initiated in response to the call for improved research by the National Academies of Sciences, Engineering, and Medicine (NASEM) (United States) Consensus Study Report on Temporomandibular Disorders (TMDs), a set of putatively localized musculoskeletal conditions. In this Special Issue, the importance of systems biology for TMDs emerges from each of three separate publications. The importance of systems biology to patients is anchored in two domains -laboratory research and clinical observation. The three publications fully speak to the underlying goals in the NASEM recommendations for initiatives: that research on TMDs needs to broaden, that integration between basic and clinical science needs to improve, and that while better evidence is needed, clinicians need to utilize the evidence that already exists. All three of these initiatives, taken together, would lead to better understanding of these complex diseases and to better care of patients with these diseases.